The Islamic Secular: Comments - Humeira Iqtidar (International Institute of Islamic Thought, 2017)
Professor Sherman A. Jackson, an authority on Islamic legal and intellectual history, has claimed in this article that a particular form of the secular is internal to Islam. For him, the secular is primarily a manifestation of the differentiation of spheres of human life. The Islamic secular, he argues, is revealed through a close reading of the boundaries that the Sharia self-imposes upon its jurisdiction and that implicitly operationalizes a type of differentiation. His argument rests upon a distinction between Sharia and the wider religion of Islam. This allows him to claim that the Sharia’s self-limitation supported a recognition of other modes of reasoning and argumentation within Islam, and that it is this space of non-Sharia reasoning that constitutes the space of the secular within Islam. Arguing for such a relationship between Sharia and the secular, then, leads him to point out that the distinction between the Islamic and the Western seculars lays not so much in the substance, but in their function. In other words, substantively both versions of the secular seem to support rational, empirical thought; however, in the case of Islam, the function of the secular is not to reduce of religion.